Overcoming poverty in Laut Tribe households through gender relations on Lipan Island, Riau Islands Province - Sri Wahyuni; Emmy Solina (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
The Laut Tribe on Lipan Island in Selayar District, Lingga Regency in the Riau Islands Province is a remote community that has received guidance from the government but they live below the poverty line. This study aimed to look at the gender relations of the Laut Tribe households in relation to overcoming the poverty problems, using a gender analysis approach. This study used a qualitative methodology with a descriptive approach. The informants of this study are the husbands and wives from Laut Tribe. The data was obtained through interviews, observations, and documentation. The results of this study showed that the women were contributors to the family’s economy, which was used to meet their daily needs. Some worked as shrimp peeler laborers and domestic servants, while others followed their husbands to go to sea to sort the catch. These women role was only considered to improve the family’s economy because of the patriarchal values constructed in the community. This has an impact on gender relations, in which there is a division of roles in the domestic and public sectors which causes the women to have a double burden and has no effect on the women’s bargaining position.